2018
DOI: 10.3390/w10121798
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Framework for Evaluating Flood Inundation Hazard under Different Dam Operation Scenarios—A Case Study in Naugatuck River

Abstract: Worldwide, many river floodplains contain critical infrastructure that is vulnerable to extreme hydrologic events. These structures are designed based on flood frequency analysis aimed at quantifying the magnitude and recurrence of the extreme events. This research topic focuses on estimating flood vulnerability at ungauged locations based on an integrative framework consisting of a distributed rainfall-runoff model forced with long-term (37 years) reanalysis meteorological data and a hydraulic model driven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…While RFFA offers a potential solution, it has to be highlighted that a fundamental prerequisite for its application is the identification of statistically homogeneous regions, which is far from being a straightforward task for applications at the scale of CONUS, where areas with large variability in climate and watershed characteristics (both natural and anthropogenic) are observed. Alternatively, future research for improving at-site FFA could therefore focus on two possible directions that aim to (a) generate long-term hydrologic information by combining reanalysis data set with distributed hydrological models (Cea & Fraga, 2018;Hardesty, Shen, Nikolopoulos, & Anagnostou, 2018) and (b) investigate new statistical approaches (Marani & Ignaccolo, 2015) that overcome the limitations from shortage of data set and obtain more reliable assessment of high quantiles.…”
Section: Discussionmentioning
confidence: 99%
“…While RFFA offers a potential solution, it has to be highlighted that a fundamental prerequisite for its application is the identification of statistically homogeneous regions, which is far from being a straightforward task for applications at the scale of CONUS, where areas with large variability in climate and watershed characteristics (both natural and anthropogenic) are observed. Alternatively, future research for improving at-site FFA could therefore focus on two possible directions that aim to (a) generate long-term hydrologic information by combining reanalysis data set with distributed hydrological models (Cea & Fraga, 2018;Hardesty, Shen, Nikolopoulos, & Anagnostou, 2018) and (b) investigate new statistical approaches (Marani & Ignaccolo, 2015) that overcome the limitations from shortage of data set and obtain more reliable assessment of high quantiles.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate the two synthetic Sandy and Florence hurricane events, we used the Weather Research and Forecasting (WRF) system (Powers et al, 2017;Skamarock et al, 2008). For the synthetic Hurricane Florence event, we used a hurricane track forecast by the National Oceanic and Atmospheric Administration (NOAA) that, as of 6 September 2018, according to the Global Forecast System (GFS) forecasts of the National Centers for Environmental Prediction (NCEP), showed landfall on Long Island and in Connecticut on 14 September as a category-1 hurricane (Higgins et al, 2000).…”
Section: Atmospheric Simulationsmentioning
confidence: 99%
“…HEC-RAS is a well-known and successfully used flood analysis tool, which can be applied with high efficiency in dam breach studies [25,34,57]. As is the case of this paper, the freely available HEC-RAS software was used (version 5.0.6), which was developed by U.S. Army Corps of Engineers (USACE).…”
Section: Dam Breach Hydraulic Modelmentioning
confidence: 99%
“…Horrit and Bates have compared the simulation algorithms of 1D and 2D variants, by applying an error identification methodology for flood simulations in HEC-RAS, LISFLOOD-FP, and TELEMAC software, and have concluded that all models have proven sufficiently accurate, but have different responses when changing the friction parameters. Furthermore, they emphasize the fact that, no matter the quality of the input data, provided the user does not properly fit the data into the appropriate geometrical description of the model, the final results of the simulation will be considerably lower accuracy [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%